Visual and Camera Sensors - Park, Kang Ryoung; Lee, Sangyoun; Kim, Euntai (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes 13 papers published in Special Issue ("Visual and Camera Sensors") of the journal Sensors. The goal of this Special Issue was to invite high-quality, state-of-the-art research papers dealing with challenging issues in visual and camera sensors.